( –6m^7 + 20m^6<span>) ÷ 2m^4 = ???
as you know
</span> –6m^7 + 20m^6 = 2m^4 (-3m^3 + 10m^2)
[2m^4 (-3m^3 + 10m^2) ] / 2m^4 (2m^4 is canceled out)
= -3m^3 + 10m^2
answer is B. –3m^3 + 10m^2
Answer:
Ok. Listen. I don't want you to cram, or ask for help at the last minute, but we will take it step by step.
Step-by-step explanation:
1. (1.6)/100=0.016
2. 2/0.016=125
3. 25% error.
Do you see why?
Answer:
a. $ 2,431.01 = 4 years
b. $ 4,584.04 = 17 years
c. 4.57 years = $ 2,499.57
d. 8.3 year = $ 2,998.48
e. $ 2,431.01 = 4 years
Step-by-step explanation:
Compound Interest Equation
A = P(1 + r/n)nt
Where:
A = Accrued Amount (principal + interest)
P = Principal Amount
I = Interest Amount
R = Annual Nominal Interest Rate in percent
r = Annual Nominal Interest Rate as a decimal
r = R/100
t = Time Involved in years, 0.5 years is calculated as 6 months, etc.
n = number of compounding periods per unit t; at the END of each period